Vaccination Controversies: An Adult Case of Post-Vaccinal Acute Disseminated Encephalomyelitis - Melo Alves, João (2019)
Acute disseminated encephalomyelitis is a rare inflammatory demyelinating multifocal disease of the central nervous system that typically occurs in children following vaccination or exanthematous viral infections and conveys an elevated risk of neurological sequelae unless promptly recognized and treated. We describe an adult case of acute disseminated encephalomyelitis following vaccination against Mumps, Measles and Rubella, presenting with fever and progressive neurological deficits which improved under systemic corticosteroid therapy. Considering the ongoing public debate regarding universal vaccination and the surge of previously controlled infectious diseases, we aim not only to underline the need for a rigorous assessment of vaccination safety on adult patients in order to prevent misguidance of public opinion, but also to alert clinicians for an early diagnosis of acute disseminated encephalomyelitis in these patients, the incidence of which we speculate may be rising.